2018
DOI: 10.20944/preprints201801.0021.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A New Biochemical Approach to Detect Oxidative Stress in Infertile Women Undergoing Assisted Reproductive Technology Procedures

Abstract: Oxidative stress negatively affects folliculogenesis and embryo development. However, a reliable and biologically accurate indicator of oxidative stress does not yet exist. On these bases, the aim of this study was to assess -and compare-blood and follicular fluid (FF) redox status in 45 infertile subjects (and 45 age-matched controls) undergoing in vitro fertilization (IVF) and to establish its connection with the outcome of IVF. Blood and FF were obtained at the time of egg retrieval and immediately analyzed… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…A number of theories have been put forward one after another to explain the potential mechanism of ovarian aging, the most classic of which is the free radical theory, which maintains that oxidative stress caused by the increase of intracellular reactive oxygen species (ROS) is the main reason for mammalian cell senescence [20,21,22,23]. In addition, many studies have shown that oxidative stress initiates the ovarian aging process and other processes that promote ovarian aging, such as inflammation, mitochondrial dysfunction, mitochondrial depolarization, endogenous apoptosis and so on [24,25,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…A number of theories have been put forward one after another to explain the potential mechanism of ovarian aging, the most classic of which is the free radical theory, which maintains that oxidative stress caused by the increase of intracellular reactive oxygen species (ROS) is the main reason for mammalian cell senescence [20,21,22,23]. In addition, many studies have shown that oxidative stress initiates the ovarian aging process and other processes that promote ovarian aging, such as inflammation, mitochondrial dysfunction, mitochondrial depolarization, endogenous apoptosis and so on [24,25,26,27].…”
Section: Introductionmentioning
confidence: 99%